Laminate, film for structure, membrane structure, structure, method for constructing membrane structure, and method for repairing membrane structure

A laminate structure with a removable protective film and adhesive layer addresses the issue of scratches in fluororesin films, ensuring protection and ease of use during construction, thereby reducing damage and construction time.

JP7604132B2Active Publication Date: 2024-12-23DENKA CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2020136836
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-13
Publication Date
2024-12-23
Estimated Expiration
2040-08-13

AI Technical Summary

Technical Problem

Fluororesin films containing ethylene monomer units, such as ECTFE, are prone to scratches during construction and handling, leading to prolonged construction times and potential damage to membrane structures used in large buildings.

Method used

A laminate structure is developed with a removable protective film laminated on both sides of a fluororesin film via an adhesive layer, ensuring a specific peel strength to prevent scratches and easy removal of the protective film without leaving residue on the fluororesin film.

Benefits of technology

The laminate structure effectively protects the fluororesin film from scratches during handling and construction, allowing for easy peeling and use of the film without adhesive residue, thus preventing damage and reducing construction time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604132000002
    Figure 0007604132000002
  • Figure 0007604132000003
    Figure 0007604132000003
  • Figure 0007604132000004
    Figure 0007604132000004
Patent Text Reader

Abstract

To prevent scratch generation on a fluorine resin film including an ethylene monomer unit.SOLUTION: There is provided a laminate in which, a protective film (B) is detachably stuck, through an adhesive layer (C), onto one or both surfaces of a fluorine resin film (A) including an ethylene monomer unit, and average detachment strength is 0.05 N / 25 mm or more and 0.50 N / 25 mm or less as of when the protective film (B) is detached, from the fluorine resin film (A), together with the adhesive layer (C), by 180° in an environment of 23°C, relative humidity of 50%, at a grip movement speed of 300 mm / min.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fluororesin film containing an ethylene monomer unit. The present invention also relates to a film for construction, a membrane structure, a building, a method for constructing a membrane structure, and a method for repairing a membrane structure, which use the fluororesin film. [Background technology]

[0002] Fluororesin films containing ethylene monomer units, such as ethylene-chlorotrifluoroethylene copolymer (hereinafter also referred to as "ECTFE") and ethylene-tetrafluoroethylene copolymer (hereinafter also referred to as "ETFE"), are used in structural parts of semiconductor manufacturing equipment, various corrosion-resistant lining materials, etc., taking advantage of their weather resistance, chemical resistance, flame retardancy, and melt moldability. In addition, since ECTFE and other resins can be extruded and molded into films, they are used in a variety of applications, such as surface protection films, solar cell component films, release films, and films for membrane structures.

[0003] Examples of prior art documents related to fluororesin films containing ethylene monomer units such as ECTFE include the following.

[0004] International Publication No. 2017 / 033701 (Patent Document 1) describes an invention aimed at providing a method for producing a resin film containing ECTFE that is excellent in transparency and appearance. This document describes that when producing a resin film from a resin composition containing ECTFE, it is possible to suppress crystallization of ECTFE while preventing a rise in the temperature of the resin composition and inclusion of foreign matter by setting the opening ratio of the breaker plate, the opening of the screen mesh, and the difference between the resin temperature at the T-die outlet and the surface temperature of the cooling roll that receives the resin discharged from the T-die outlet within specific ranges.

[0005] Patent Document 1 also describes the use of a resin film containing ECTFE as a surface protection film for a substrate. In this case, it describes that after surface modification is performed to impart adhesiveness to the resin film, an adhesive resin is applied to the surface of the surface-modified resin film, and the film is laminated on the substrate.

[0006] WO 2018 / 066584 (Patent Document 2) proposes the addition of a bisphenol-based antioxidant to provide an ECTFE resin composition that can maintain excellent transparency and is less likely to yellow. It also describes that the ECTFE resin composition can be molded into a sheet, and that the sheet can be suitably used for a membrane structure. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2017 / 033701 [Patent Document 2] International Publication No. 2018 / 066584 Summary of the Invention [Problem to be solved by the invention]

[0008] As mentioned above, fluororesin films containing ethylene monomer units such as ECTFE can be applied to membrane structures, but their practicality has not been fully studied. For example, membrane structures are often applied to relatively large buildings such as sports facilities and commercial facilities, and there is a problem that they are easily damaged during construction. For example, scratches occur in various situations, such as when the film is unfolded, when people walk on the film, when multiple films are joined, and when a film with a large area due to the joining of multiple films is rolled up for transportation, and care must be taken when handling the film. There is also a concern that construction time will be extended as a result of careful construction to prevent scratches.

[0009] The present invention has been made in view of the above circumstances, and an object of the present invention is to prevent the occurrence of scratches in a fluororesin film containing an ethylene monomer unit in one embodiment. In another embodiment, the present invention also has an object of providing a film for buildings, a membrane structure, a building, a method for constructing a membrane structure, and a method for repairing a membrane structure, which use the fluororesin film. [Means for solving the problem]

[0010] As a result of various studies conducted to solve the above problems, the inventors discovered that it is effective to attach a peelable protective film together with an adhesive layer to one or both sides of a fluororesin film containing ethylene monomer units, and arrived at the present invention, which is exemplified below.

[0011] [1] A laminate in which a protective film (B) is releasably attached via an adhesive layer (C) to one or both sides of a fluororesin film (A) containing an ethylene monomer unit, wherein the average peel strength when the protective film (B) together with the adhesive layer (C) is peeled off from the fluororesin film (A) at an angle of 180° at a gripping movement speed of 300 mm / min in an environment of 23°C and a relative humidity of 50% is 0.05 N / 25 mm or more and 0.50 N / 25 mm or less. [2] The laminate according to [1], wherein the fluororesin film (A) is a film containing either one or both of an ethylene-chlorotrifluoroethylene copolymer and an ethylene-tetrafluoroethylene copolymer. [3] The laminate according to [1] or [2], wherein the adhesive layer (C) has a thickness of 1 to 20 μm, and the protective film (B) has a thickness of 20 to 80 μm. [4] The laminate according to any one of [1] to [3], wherein the fluororesin film (A) has a thickness of 50 μm or more and 500 μm or less. [5] The laminate according to any one of [1] to [4], wherein the protective film (B) contains either one or both of a polyethylene-based resin and a polypropylene-based resin, and the adhesive layer (C) contains a (meth)acrylic adhesive. [6] The laminate according to any one of [1] to [5], which is wound into a roll. [7] A film for construction, obtained by peeling off the protective film (B) from the laminate according to any one of [1] to [6]. [8] A membrane structure comprising the architectural film described in [7]. [9] A building comprising the membrane structure described in [8].

[10] The laminate according to any one of [1] to [6], wherein a protective film (B) is bonded to one surface of a fluororesin-based film (A) via an adhesive layer (C), and a silicone-based adhesive layer (E) is provided on the other surface.

[11] The laminate according to

[10] , wherein a separator (F) is attached to the surface of the silicone-based adhesive layer (E) that is not in contact with the fluororesin-based film (A).

[12] The laminate according to any one of items

[10] to

[12] , which is in the form of a tape.

[13] A step of preparing a plurality of laminates according to any one of [1] to [6]; a step of partially peeling off the protective film (B) at each end of the plurality of laminates to expose the fluororesin film (A); a step of overlapping and heat-sealing the fluororesin films (A) exposed at the respective ends of the laminate to form a bonded body in which a plurality of the laminates are bonded together; A step of extending the joint body on a body; peeling the unpeeled protective film (B) from the bonded body; A method for constructing a membrane structure comprising the steps of:

[14] A step of preparing a laminate according to

[10] or

[11] ; If the separator (F) is attached, peeling the separator (F) from the laminate; a step of attaching the laminate to a membrane portion of a membrane structure to be repaired so that the silicone-based adhesive layer (E) serves as an attachment surface; peeling the protective film (B) from the laminate attached to the membrane portion; A method for repairing a membrane structure comprising the steps of: Effect of the Invention

[0012] The laminate according to one embodiment of the present invention comprises a protective film (B) attached with a suitable peel strength to one or both surfaces of a fluororesin film (A) containing an ethylene monomer unit. Therefore, the surface of the fluororesin film (A) can be prevented from being damaged in various processes (packaging, transportation, application, etc.) before the protective film (B) is peeled off, and the protective film (B) can be easily peeled off to use the fluororesin film (A) when necessary. The protective film (B) can be peeled off together with the adhesive layer (C), and since almost no adhesive layer (C) remains on the surface of the fluororesin film (A), there is no need to remove the adhesive layer (C) separately. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic cross-sectional view showing a laminate structure of a laminate according to a first embodiment of the present invention. [Diagram 2] FIG. 4 is a schematic cross-sectional view showing a laminate structure of a laminate according to a second embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic side view for explaining a step of forming a bonded body in which a plurality of laminates according to the first embodiment are bonded together. [Figure 4] FIG. 2 is a schematic side view of a production apparatus used for producing the laminates of Comparative Examples 3 to 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, embodiments of the present invention will be described. The embodiments described below are illustrative of typical embodiments of the present invention, and are not intended to narrow the technical scope of the present invention.

[0015] 1. First Embodiment Referring to Fig. 1, the laminate (1) according to the first embodiment has a protective film (B) peelably attached to one or both surfaces of a fluororesin film (A) containing an ethylene monomer unit via an adhesive layer (C). The fluororesin film (A) is peelably attached to one or both surfaces of the protective film (B), so that the protective film (B) can be peeled off when necessary. For example, the protective film (B) can be peeled off and the fluororesin film (A) can be used.

[0016] The form of the laminate (1) according to the first embodiment is not particularly limited, and it can be provided, for example, in a form wound in a roll, in a form of a sheet cut to a predetermined size, etc. When used as a film for buildings, which will be described later, a large area is required, so it is convenient to provide it in a form wound in a roll and unwind it for use.

[0017] In the laminate (1) according to the first embodiment, the protective film (B) can be peeled off together with the adhesive layer (C) from the fluororesin film (A). In other words, in the laminate (1) according to the first embodiment, the peel strength between the fluororesin film (A) and the adhesive layer (C) is smaller than the peel strength between the protective film (B) and the adhesive layer (C). When the adhesive layer (C) is peeled off from the fluororesin film (A) by peeling off the protective film (B), the adhesive layer (C) does not substantially remain on the surface of the fluororesin film (A), so there is no need to remove the adhesive layer (C) separately. The peel strength between the protective film (B) and the adhesive layer (C) can be increased, if necessary, by subjecting the surface of the protective film (B) in contact with the adhesive layer (C) to a surface modification treatment such as a corona treatment and a plasma treatment.

[0018] The peel strength when peeling the protective film (B) together with the adhesive layer (C) from the fluororesin film (A) is preferably high from the viewpoint of preventing unintended peeling during packaging, transportation, or application. On the other hand, if the peel strength is too high, the usability is deteriorated, and the fluororesin film (A) may be deformed during peeling, or the adhesive layer (C) may remain significantly on the surface of the fluororesin film (A). From this viewpoint, the average peel strength when peeling the protective film (B) together with the adhesive layer (C) from the fluororesin film (A) at 180° at a gripping speed of 300 mm / min under an environment of 23°C and relative humidity of 50% is preferably 0.05 N / 25 mm or more and 0.50 N / 25 mm or less. The lower limit of the average peel strength is preferably 0.07 N / 25 mm or more, more preferably 0.10 N / 25 mm or more. The upper limit of the average peel strength is preferably 0.45 N / 25 mm or less, and more preferably 0.40 N / 25 mm or less.

[0019] The above 180° peel test is performed according to the following procedure. First, when the fluororesin film (A) is on the inside, the excess layer is peeled off in advance so that the fluororesin film (A) is exposed. For example, in the case of the laminate (1) shown in FIG. 1, the protective film (B) on the side opposite to the side for which the peel strength is to be determined is peeled off, and in the case of the laminate (2) shown in FIG. 2, the separator (F) is peeled off. After peeling, there is no problem even if the adhesive layer (C) or the silicone adhesive layer (E) remains. Next, the fluororesin film (A) side of the laminate sample is fixed to a SUS plate with a strong double-sided tape. The protective film (B) is peeled off slightly from the laminate sample. Next, the SUS plate and the protective film (B) are each chucked, and a 180° peel test is performed under the following conditions: temperature: 23°C, relative humidity: 50%, sample size: length 150 mm x width 25 mm, gripping movement speed: 300 mm / min, and the average peel strength is determined. Other conditions are in accordance with JIS K6854-2:1999. At least five samples are prepared, and the arithmetic mean of the average peel strength is taken as the measured value.

[0020] Examples of the fluororesin containing an ethylene monomer unit contained in the fluororesin-based film (A) include, but are not limited to, ethylene-chlorotrifluoroethylene copolymer (ECTFE), ethylene-tetrafluoroethylene copolymer (ETFE), and ethylene-tetrafluoroethylene-hexafluoropropylene copolymer (EFEP). The fluororesin containing an ethylene monomer unit contained in the fluororesin-based film (A) may be one type or two or more types. Among these, the fluororesin-based film (A) preferably contains either one or both of ethylene-chlorotrifluoroethylene copolymer (ECTFE) and ethylene-tetrafluoroethylene copolymer (ETFE) for the reason of heat resistance, and more preferably contains ethylene-chlorotrifluoroethylene copolymer (ECTFE) for the reason of flame retardancy and transparency.

[0021] In one embodiment, the fluororesin film (A) preferably contains 80% by mass or more of a fluororesin containing an ethylene monomer unit, more preferably 90% by mass or more, and even more preferably 95% by mass or more. In another embodiment, the fluororesin film (A) preferably contains one or both of ECTFE and ETFE in total in an amount of 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more. In yet another embodiment, the fluororesin film (A) preferably contains 80% by mass or more of ECTFE, more preferably 90% by mass or more, and even more preferably 95% by mass or more.

[0022] As ECTFE, in addition to a copolymer using two monomers, ethylene (hereinafter also referred to as "Et") and chlorotrifluoroethylene (hereinafter also referred to as "CTFE"), a copolymer using, in addition to the above monomers, one or more of (perfluorohexyl)ethylene, (perfluorobutyl)ethylene, (perfluorooctyl)ethylene, [4-(heptafluoroisopropyl)perfluorobutyl]ethylene, perfluoroalkyl vinyl ether, etc. as a third monomer can be used.

[0023] The monomer ratio (molar ratio) of Et and CTFE in ECTFE is not particularly limited, but is preferably Et / CTFE=30 / 70 to 70 / 30, more preferably 40 / 60 to 60 / 40. When Et / CTFE is 70 / 30 or less, it is possible to prevent the transparency, weather resistance, antifouling properties, etc., which are characteristics of fluororesins, from being impaired. In addition, when Et / CTFE is 30 / 70 or more, it is possible to suppress the amount of acid gas generated during high-temperature use.

[0024] As ETFE, in addition to a copolymer using two monomers, ethylene (hereinafter also referred to as "Et") and tetrafluoroethylene (hereinafter also referred to as "TFE"), a copolymer using, in addition to the above monomers, one or more of (perfluorohexyl)ethylene, (perfluorobutyl)ethylene, (perfluorooctyl)ethylene, [4-(heptafluoroisopropyl)perfluorobutyl]ethylene, perfluoroalkyl vinyl ether, etc. as a third monomer can be used.

[0025] The monomer ratio (molar ratio) of Et and TFE in ETFE is not particularly limited, but is preferably Et / TFE=30 / 70 to 70 / 30, more preferably 40 / 60 to 60 / 40. When Et / TFE is 70 / 30 or less, the transparency, weather resistance, antifouling properties, etc., which are characteristics of fluororesins, can be prevented from being impaired. Also, when Et / TFE is 30 / 70 or more, the amount of acid gas generated during high-temperature use can be suppressed.

[0026] Examples of ethylene-chlorotrifluoroethylene copolymer (ECTFE) and ethylene-tetrafluoroethylene copolymer (ETFE) include random copolymers, alternating copolymers, graft copolymers, block copolymers (e.g., linear types such as diblock copolymers, triblock copolymers, gradient copolymers, and star copolymers polymerized by the arm-first method or core-first method), copolymers obtained by polymerization using macromonomers, which are polymerizable functional compounds (macromonomer copolymers), and mixtures thereof. Among these, from the viewpoint of resin productivity, alternating copolymers are preferred.

[0027] The fluororesin film (A) may contain one or more antioxidants within the scope of the present invention. Examples of the antioxidant include, but are not limited to, phenol-based antioxidants and phosphorus-based antioxidants.

[0028] As the phenol-based antioxidant, for example, alkyl-substituted bisphenol-based antioxidants such as 3,9-bis[2-{3-(tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane, 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), and 2,2'-bis(4-hydroxyphenyl)propane can be suitably used.

[0029] The amount of the phenol-based antioxidant added to the fluororesin film (A) is not particularly limited, but is preferably 0.01 to 1.0 mass%, more preferably 0.01 to 0.5 mass%, based on the mass of the fluororesin film (A). When it is 1.0 mass% or less, yellowing of the fluororesin film (A) can be suppressed and the transparency can be prevented from decreasing too much. When it is 0.01 mass% or more, the acid gas reduction effect can be significantly obtained.

[0030] As the phosphorus-based antioxidant, phosphite-based antioxidants such as 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, 6-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-t-butyldibenzo[d,f][1,3,2]dioxaphosphorin, tris(2,4-di-tert-butylphenyl) phosphite, 3,9-bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, tris(4-nonylphenyl) phosphite, diphenyl(2-ethylhexyl) phosphite, and diphenylisodecylphosphite can be suitably used.

[0031] The amount of the phosphorus-based antioxidant added to the fluororesin film (A) is not particularly limited, but is preferably 0.01 to 1.0 mass%, more preferably 0.01 to 0.5 mass%, based on the mass of the fluororesin film (A). When it is 1.0 mass% or less, yellowing of the fluororesin film (A) can be suppressed and the transparency can be prevented from decreasing too much. When it is 0.01 mass% or more, the acid gas reduction effect can be significantly obtained.

[0032] To the fluororesin film (A), one or more resins other than fluororesins containing ethylene monomer units may be added, as long as the object of the present invention is not impaired. Examples of such resins include polychlorotrifluoroethylene (PCTFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene (PTFE), polyhexafluoropropylene (HFP), polyperfluoroalkylvinyl ether (PFA), vinylidene fluoride, and terpolymers of tetrafluoroethylene, vinylidene fluoride, and hexafluoropropylene.

[0033] Furthermore, the fluororesin film (A) may contain, as appropriate, plasticizers, heat stabilizers, ultraviolet absorbers, light stabilizers, crystal nucleating agents, antiblocking agents, sealability improvers, release agents, colorants, pigments, foaming agents, flame retardants, etc., within the scope of the object of the present invention.

[0034] The haze of the fluororesin film (A) measured according to JIS K7136:2000 is preferably 20% or less, more preferably 10% or less, even more preferably 5% or less, and most preferably 2% or less, from the viewpoint of increasing transparency, and may be, for example, in the range of 0.1 to 20%. However, this does not apply when a matting agent such as crosslinked acrylic fine particles, silica particles, or polysiloxane particles is added to intentionally increase the haze from the viewpoint of design.

[0035] From the viewpoint of enhancing transparency, the total light transmittance of the fluororesin film (A) measured in accordance with JIS K7375:2008 is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more, and can be, for example, 80 to 95%.

[0036] The thickness of the fluororesin film (A) is not particularly limited, but is preferably 50 to 500 μm, more preferably 100 to 400 μm, even more preferably 200 to 300 μm, and particularly preferably 250 to 300 μm. From the viewpoint of handling, it is preferable that the thickness of the fluororesin film (A) is 50 μm or more. In addition, the thickness of the fluororesin film (A) is 500 μm or less, which contributes to cost reduction.

[0037] The fluororesin film (A) can be produced, for example, by a method of melt extrusion molding into a film from a T-die. As the extruder, a single screw type, a twin screw type, a tandem type, etc. can be generally used, but a single screw type extruder is preferred in terms of preventing the resin from stagnation in the extruder system. The screw shape used in the single screw type extruder is not particularly limited as long as it is configured not to cause excessive shear heat, but a full flight screw is more preferred in terms of melt extrusion without applying excessive shear. From the viewpoint of expressing transparency, it is preferable that the film extruded from the T-die immediately contacts a cooling roll close to the T-die and is taken up while being cooled. Thereafter, the fluororesin film (A) can be wound into a roll. The thickness of the film can be controlled by adjusting the distance between the lip openings of the T-die and adjusting the winding speed.

[0038] The protective film (B) has a function of protecting the fluororesin film (A). In addition, the protective film (B) adheres to the adhesive layer (C) with sufficient peeling strength, and therefore has a function of peeling off the protective film (B) together with the adhesive layer (C) when peeling it off from the fluororesin film (A). There are no particular limitations on the constituent material of the protective film (B) as long as it achieves the above function, but it is expected that it will be discarded or recycled after peeling, so it is desirable that it is composed of an inexpensive material. Furthermore, it is desirable that the protective film (B) has a certain degree of flexibility and does not break or float when wound into a roll.

[0039] The protective film (B) can be provided as, for example, a resin film, but is not limited thereto. In view of the above function, the protective film (B) can contain, for example, a polyolefin resin such as a polyethylene resin, a polypropylene resin, a polymethylpentene resin, or an ethylene-propylene copolymer, a polyvinyl chloride resin, a polyvinylidene chloride resin, a polyvinyl fluoride resin, a polyvinylidene fluoride resin, a polystyrene resin such as an acrylonitrile-styrene copolymer or an acrylonitrile-butadiene-styrene copolymer, a (meth)acrylic resin, a polycarbonate resin, a polyamide resin, or a polyester resin. The protective film (B) may contain one of these resins, or may contain two or more of them. Among these, it is preferable that the protective film (B) contains either one or both of a polyethylene resin and a polypropylene resin for the reason of flexibility. In addition to the above, the protective film (B) may be made of paper.

[0040] In one embodiment, the protective film (B) preferably contains 80% by mass or more of the resin component, more preferably 90% by mass or more, and even more preferably 95% by mass or more. In another embodiment, the protective film (B) preferably contains 80% by mass or more of the polyolefin resin in total, more preferably 90% by mass or more, and even more preferably 95% by mass or more. In yet another embodiment, the protective film (B) preferably contains 80% by mass or more of either or both of the polyethylene resin and the polypropylene resin in total, more preferably 90% by mass or more, and even more preferably 95% by mass or more.

[0041] The protective film (B) may contain, as appropriate, antioxidants, plasticizers, heat stabilizers, ultraviolet absorbers, light stabilizers, crystal nucleating agents, antiblocking agents, sealability improvers, release agents, colorants, pigments, foaming agents, flame retardants, etc., within the scope of the invention.

[0042] The thickness of the protective film (B) is preferably 20 to 80 μm, more preferably 25 to 75 μm, even more preferably 30 to 70 μm, and particularly preferably 40 to 65 μm. When the thickness of the protective film (B) is 20 μm or more, the handling property during lamination is excellent. In addition, by making the thickness of the B layer 80 μm or less, the diameter of the roll when wound into a roll does not become too large.

[0043] For example, the protective film (B) can be produced by melt extrusion molding into a film from a T-die, similarly to the fluororesin film (A).

[0044] The adhesive layer (C) is a layer composed of an adhesive, and is required to be fixed to the protective film (B) with a peel strength greater than that of the fluororesin film (A). Examples of adhesives include rubber-based adhesives, (meth)acrylic adhesives, silicone-based adhesives, urethane-based adhesives, vinyl alkyl ether-based adhesives, polyvinyl alcohol-based adhesives, polyvinylpyrrolidone-based adhesives, polyacrylamide-based adhesives, and cellulose-based adhesives. Such adhesives may be used alone or in combination of two or more. (Meth)acrylic means one or both of acrylic and methacrylic. Details of (meth)acrylic adhesives suitable for use in the present invention are described in International Publication No. 2016 / 010013. Among these, (meth)acrylic adhesives are preferred because of the ease of adjusting the adhesive strength.

[0045] Pressure-sensitive adhesives can be classified according to their adhesive form into hot melt adhesives, pressure-sensitive adhesives, two-part mixture adhesives, heat-curing adhesives, UV-curing adhesives, etc. Of these, pressure-sensitive adhesives are preferred because they do not require devices that emit heat or UV light.

[0046] Specific examples of the (meth)acrylic adhesive include C2 to C6 (meth)acrylic acids such as ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, 2-methylbutyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, and isononyl (meth)acrylate. 12 A copolymer of at least one alkyl ester (monomer A) and at least one functional group-containing acrylic monomer (monomer B) such as acrylic acid, methacrylic acid, acrylamide, N-methylolacrylamide, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, etc. can be suitably used. The copolymerization ratio of the monomer A and the monomer B is, expressed as a mass ratio, monomer A / monomer B=99.9 / 0.1 to 70 / 30, preferably 99 / 1 to 75 / 25, in 100 parts by mass of the total of the monomer A and the monomer B.

[0047] Particularly suitable (meth)acrylic copolymers include copolymers of butyl acrylate (BA) and acrylic acid (AA). In this case, the copolymerization ratio of butyl acrylate (BA) and acrylic acid (AA) is BA / AA=99.9 / 0.1 to 70 / 30, preferably 99.5 / 0.5 to 80 / 20, expressed as a mass ratio in 100 parts by mass of BA and AA in total. When AA is 0.1 parts by mass or more in 100 parts by mass of BA and AA in total, it becomes easy to control the adhesive properties by using a crosslinking agent in combination. In addition, when AA is 30 parts by mass or less in 100 parts by mass of BA and AA in total, the glass transition point (Tg) is lowered, adhesion at low temperatures is improved, and workability is also improved.

[0048] Additives such as a crosslinking agent, a tackifier, an ultraviolet absorber, and a light stabilizer can be added to the pressure-sensitive adhesive as required.

[0049] The adhesive layer (C) can be formed by a general method. For example, there is a method in which an adhesive is directly applied to the bonding surface of the protective film (B) with the fluororesin film (A) and then dried (direct coating method). There is also a method in which an adhesive is applied to a separator, dried, and then bonded to the bonding surface of the protective film (B) with the fluororesin film (A).

[0050] The pressure-sensitive adhesive can be applied using a conventionally known coating device such as a gravure roll coater, a die coater, a bar coater, a doctor blade, a comma coater, a reverse coater, etc. The pressure-sensitive adhesive may also be applied by impregnation, a curtain coating method, etc. The pressure-sensitive adhesive may be applied while cooling, heating, or irradiating with electron beams as necessary.

[0051] Drying after coating of the adhesive is preferably performed under heating from the viewpoints of promoting the crosslinking reaction, improving production efficiency, etc. The drying temperature is, for example, preferably 40° C. or higher (usually 60° C. or higher) and 150° C. or lower (usually 130° C. or lower).

[0052] In the process of forming the adhesive layer (C), after the adhesive is applied and dried, aging may be performed for the purposes of adjusting the migration of components within the adhesive layer (C), progressing the crosslinking reaction, and alleviating distortion that may exist within the adhesive layer (C).

[0053] The thickness of the adhesive layer (C) is not particularly limited. In general, as the thickness of the adhesive layer (C) becomes smaller, the adhesion to the adherend tends to decrease, so the thickness of the adhesive layer (C) can be appropriately controlled for the purpose of adjusting the peel strength. For example, the thickness of the adhesive layer (C) is preferably 1 to 20 μm, more preferably 3 to 15 μm, and even more preferably 5 to 10 μm. The above thickness means the thickness (μm / Dry) of the adhesive after drying.

[0054] The method for producing the laminate in which the fluororesin film (A) and the protective film (B) are peelably laminated via the adhesive layer (C) is not limited, but for example, the laminate can be produced by producing the fluororesin film (A) and then laminating the protective film (B) and the fluororesin film (A) via the adhesive layer (C) in a separate line. The lamination method can be, for example, a roll-type lamination method. The lamination conditions when carrying out the roll-type lamination method can be appropriately adjusted within the range of, for example, an environmental temperature of 23 to 30°C, a relative humidity of 40 to 60%, a pinch pressure of 0.2 to 1.0 MPa, a line speed of 5 to 20 m / min, and a pressure application time of 0.1 to 1 second. The peel strength between the protective film (B) and the adhesive layer (C) can be increased, if necessary, by performing a surface treatment such as a corona treatment or a plasma treatment on the bonding surface of the protective film (B) with the adhesive layer (C).

[0055] 2. Second Embodiment 2, the laminate (2) according to the second embodiment has a protective film (B) attached to one side of a fluororesin film (A) via an adhesive layer (C), and a silicone adhesive layer (E) provided on the other side. By providing the silicone adhesive layer (E), the laminate (2) according to the second embodiment can be attached to an article via the silicone adhesive layer (E).

[0056] The fluororesin film (A), protective film (B) and adhesive layer (C) in the laminate (2) according to the second embodiment are the same as those described in the first embodiment, including their mutual relationships such as peel strength, and therefore a duplicated description will be omitted.

[0057] The silicone adhesive layer (E) is a layer composed of a silicone adhesive. Silicone adhesives have excellent weather resistance and are advantageous in that they have excellent adhesion to fluororesin films compared to other adhesives. Silicone adhesives contain, for example, silicone gum, MQ resin, organic solvent, and a crosslinking agent containing a hydrosilyl group (SiH group), as well as a curing catalyst used as needed. MQ resin is a polymer having a three-dimensional structure synthesized from a monofunctional monomer (M unit) and a tetrafunctional monomer (Q unit). The number-average molecular weight of the polymer having a three-dimensional structure is preferably 10 to 100,000, more preferably 100 to 10,000. As the organic group of the monomer of each functional group, it is preferable to use a methyl group, but in the case of an addition reaction type silicone resin, it is preferable to use an alkenyl group.

[0058] Additives such as crosslinking agents, tackifiers, ultraviolet absorbers, and light stabilizers can be added to the silicone-based pressure-sensitive adhesives as required.

[0059] A separator (F) may be attached to the surface of the silicone adhesive layer (E) that is not in contact with the fluororesin film (A). By attaching the separator (F), it is possible to protect the silicone adhesive layer (E) until the step of attaching the laminate (2) to an article is performed. Examples of the separator (F) include release paper and release film. In one embodiment, the release paper has a paper substrate and a release layer formed on the surface of the paper. In one embodiment, the release film has a resin film substrate and a release layer formed on the surface of the resin film. Examples of materials for the resin film include polyethylene terephthalate (PET), biaxially oriented polypropylene (OPP), and polyethylene (PE). The release layer can contain, for example, a solvent-based, solventless, or emulsion-based silicone resin. A sealing layer may be present between the substrate and the release layer.

[0060] The silicone adhesive layer (E) can be formed by a general method. For example, there is a method (direct coating method) in which a silicone adhesive is directly applied to the other surface of the fluororesin film (A) and dried. There is also a method in which a silicone adhesive is applied to the separator (F), dried, and then laminated to the other surface of the fluororesin film (A).

[0061] When the separator (F) is peeled off later, it is desirable that the silicone adhesive layer (E) can be peeled off while being fixed to the fluororesin film (A). That is, it is desirable that the peel strength between the silicone adhesive layer (E) and the separator (F) is smaller than the peel strength between the silicone adhesive layer (E) and the fluororesin film (A). Therefore, in order to increase the peel strength between the silicone adhesive layer (E) and the fluororesin film (A), for example, a surface modification treatment such as a corona treatment or a plasma treatment may be performed on the surface of the fluororesin film (A) that contacts the silicone adhesive layer (E). It is also possible to reduce the peel strength between the silicone adhesive layer (E) and the separator (F) by coating the surface of the separator (F) that contacts the silicone adhesive layer (E) with a release agent or the like.

[0062] The silicone-based adhesive can be applied using a conventionally known coating device such as a gravure roll coater, a die coater, a bar coater, a doctor blade, a comma coater, a reverse coater, etc. The silicone-based adhesive may also be applied by impregnation, a curtain coating method, etc. The adhesive may be applied while cooling, heating, or irradiating with electron beams as necessary.

[0063] Drying after coating of the silicone-based pressure-sensitive adhesive is preferably carried out under heating from the viewpoints of promoting the crosslinking reaction, improving production efficiency, etc. The drying temperature is, for example, preferably 40° C. or higher (usually 60° C. or higher) and 150° C. or lower (usually 130° C. or lower).

[0064] In the process of forming the silicone-based adhesive layer (E), after the adhesive is applied and dried, aging may be performed for the purposes of adjusting the migration of components within the silicone-based adhesive layer (E), progressing the crosslinking reaction, and alleviating distortion that may exist within the silicone-based adhesive layer (E).

[0065] The thickness of the silicone adhesive layer (E) is not particularly limited. In general, as the thickness of the silicone adhesive layer (E) becomes smaller, the adhesion to the adherend tends to decrease, so the thickness of the silicone adhesive layer (E) can be appropriately controlled for the purpose of adjusting the peel strength. For example, the thickness of the silicone adhesive layer (E) is preferably 5 to 100 μm, more preferably 10 to 60 μm, and even more preferably 30 to 50 μm. The above thickness means the thickness (μm / Dry) of the adhesive after drying.

[0066] The thickness of the separator (F) is not particularly limited, but is preferably 20 to 100 μm, more preferably 30 to 70 μm, and even more preferably 40 to 60 μm. From the viewpoint of handling, it is preferable that the thickness of the separator (F) is 20 μm or more. In addition, the thickness of the separator (F) is 100 μm or less, which contributes to cost reduction.

[0067] (3.Applications) The use of the laminate according to the first embodiment and the second embodiment is not particularly limited, but for example, it can be used as a film for buildings by peeling off the protective film (B). The laminate according to the first embodiment can be suitably used for the construction of a membrane structure. The laminate according to the second embodiment can be suitably used for repair work of the membrane part constituting the membrane structure. Therefore, according to one embodiment of the present invention, a membrane structure including a film for buildings is provided, and according to another embodiment of the present invention, a building including such a membrane structure is provided. Examples of the membrane structure include roofing materials, wall materials, window materials, and covering materials for buildings. Examples of the building include sports facilities such as pools, athletics, soccer stadiums, baseball stadiums, and gymnasiums, airports, stations, expressways, sidewalks, bus terminals, bus and taxi stands, carports, warehouses, assembly halls, exhibition centers, aquaculture facilities, horticultural facilities (including large agricultural greenhouses and pipe houses), automobiles, and ships.

[0068] There is no particular restriction on the timing of peeling off the protective film (B) from the laminate, but for example, when constructing a membrane structure, it is desirable to peel off the protective film after spreading it on the framework from the viewpoint of protecting the fluororesin-based film (A). For example, a method of constructing a membrane structure using the laminate according to the first embodiment includes a step of partially peeling off the protective film (B) at the end of the laminate and then spreading it on the framework, and a step of peeling off the unpeeled protective film (B). There is no particular restriction on the method of spreading it on the framework, but an example is a method in which the end of the fluororesin-based film (A) exposed by partially peeling off the protective film (B) is attached to a tensioning metal fitting fixed to the framework such as a pillar or a frame.

[0069] When the tension fitting has a clamping portion, in order to make it easier to fix it to the tension fitting, the end of the fluororesin film (A) can be folded and a core material such as a wire can be passed through the internal space of the folded portion. The tip of the folded portion can be fixed by heat sealing.

[0070] When constructing a large-area membrane structure, it may be necessary to use a plurality of laminates according to the first embodiment by joining them together. In such a case, according to one embodiment of the present invention, the following membrane structure construction method is provided. A step of preparing a plurality of laminates according to the first embodiment; a step of partially peeling off the protective film (B) at each end of the plurality of laminates to expose the fluororesin film (A); a step of overlapping and heat-sealing the fluororesin films (A) exposed at each end of the laminate to each other to form a bonded body in which a plurality of the laminates are bonded together; A step of extending the joint body on a body; peeling the unpeeled protective film (B) from the bonded body; A method for constructing a membrane structure comprising the steps of:

[0071] 3 is a schematic side view for explaining a process for forming a bonded body in which a plurality of laminates are bonded together. Here, a state is shown in which two fluororesin films (A) exposed by partially peeling off the protective film (B) are heat-sealed at the ends of each of the two laminates (1) according to the first embodiment. After the fluororesin films (A) are overlapped and heat-sealed, a protective film (B) may be attached again to the exposed portion of the fluororesin film (A) until the process for peeling off the entire protective film (B) is performed.

[0072] In some cases, cracks or holes may occur in the membrane portion of a membrane structure, and in such cases, it is desirable to be able to easily repair them. According to one embodiment of the present invention, the following membrane structure repair method is provided. preparing a laminate according to a second embodiment; If a separator (F) is attached, a step of peeling the separator (F) from the laminate; a step of attaching the laminate to a membrane portion of a membrane structure to be repaired so that the silicone-based adhesive layer (E) serves as an attachment surface; peeling the protective film (B) from the laminate attached to the membrane portion; A method for repairing a membrane structure comprising the steps of:

[0073] The size and shape of the laminate may be adjusted as appropriate to suit the size and shape of the membrane portion to be repaired, but from the viewpoint of versatility, it is preferable to provide the laminate in the form of, for example, a long roll tape. EXAMPLES

[0074] The present invention will be described in detail below based on examples and comparative examples.

[0075] <1. Preparation of Laminates According to Examples 1 to 10> (1-1. Preparation of fluororesin film (A)) <ECTFEフィルム> 100 parts by mass of ECTFE resin ("Halar ECTFE 700HC" manufactured by Solvay) was premixed with 0.2 parts by mass of a phenol-based antioxidant (Sumitomo Chemical Co., Ltd., Sumilizer GA-80) and 0.2 parts by mass of a phosphorus-based antioxidant (Sumitomo Chemical Co., Ltd., Sumilizer GP). The premix was melt-mixed at 250°C using a φ30mm twin-screw extruder (manufactured by Kobe Steel, Ltd., L / D=44), extruded into a strand shape, cooled, and pelletized into pellets that were uniformly mixed with a pelletizer. The pellets were then melt-mixed in a 65mm single-screw extruder (manufactured by GM Engineering Co., Ltd., L / D=25) using a full-flight screw with a compression ratio of 2.3 at a set temperature of the extruder that allows sufficient plasticization, and then extruded into a film using a coat hanger type T-die (set temperature 250°C, sheet width 1200mm, downward discharge type). The fluororesin film (A) extruded from the T-die was immediately taken up while being inserted between a casting roll (cooling water set temperature 40°C) and a touch roll (cooling water set temperature 40°C) adjacent to the T-die. The fluororesin film (A) thus obtained moved along the rotation direction of the casting roll, was cooled by being transported onto a cooling roll (cooling water set temperature 30°C), and was finally taken up by a reel. The thickness of the fluororesin film (A) shown in Table 1 is the average value measured at any five points with a dial sheet gauge. <ETFEフィルム> An ETFE film (manufactured by Nowofol (product number Nowoflon ET6235Z)) was prepared. The thickness of the fluororesin film (A) shown in Table 1 is the average value measured at any five points with a dial sheet gauge.

[0076] (1-2. Preparation of protective film (B)) The following pressure-sensitive adhesive type protective film (B) was prepared. An adhesive layer (C) is laminated on one side of the protective film (B), and each part number has a different base thickness and adhesive strength. The thicknesses of the protective film (B) and adhesive layer (C) listed in Table 1 are the average values ​​measured at five random points using a dial sheet gauge. (1) DMF masking film manufactured by Daio Kakoshi Kogyo Co., Ltd. (product number: FM-115, base material: polyethylene resin, adhesive: acrylic adhesive) (2) DMF masking film manufactured by Daio Kakoshi Kogyo Co., Ltd. (product number: FM-125, base material: polyethylene resin, adhesive: acrylic adhesive) (3) DMF masking film manufactured by Daio Kakoshi Kogyo Co., Ltd. (product number: FM-315, base material: polypropylene resin, adhesive: acrylic adhesive) (4) DMF masking film manufactured by Daio Kakoshi Kogyo Co., Ltd. (product number: FM-330, base material: polypropylene resin, adhesive: acrylic adhesive) (5) DMF masking film manufactured by Daio Kakoshi Kogyo Co., Ltd. (product number: FM-315D, base material: polypropylene resin, adhesive: acrylic adhesive)

[0077] (1-3. Preparation of Laminate) The protective film (B) with adhesive layer (C) prepared above was laminated on one side of the fluororesin film (A) prepared above, with the adhesive layer (C) facing inward, and a pinch pressure of 0.5 MPa was applied for 0.5 seconds using a roll laminator at an environmental temperature of 23°C, a relative humidity of 50%, and a line speed of 10 m / min to produce a laminate. The combination of the fluororesin film (A) and the protective film (B) was changed according to the test number as shown in Table 1.

[0078] <2. Films according to Comparative Examples 1 and 2> The ECTFE film (Comparative Example 1) and the ETFE film (Comparative Example 2) prepared in Example 1 were used as they were.

[0079] <3. Films according to Comparative Examples 3 to 6> (3-1. Preparation of protective film (B)) The following self-adhesive type protective films (B) were prepared. These protective films (B) do not have an adhesive layer. The thickness of the protective film (B) listed in Table 1 is the average value measured at five random points using a dial sheet gauge. (1) DMF masking film manufactured by Daio Kakoshi Kogyo Co., Ltd. (product number: FM-4000, base material: polyolefin resin) (2) DMF masking film manufactured by Daio Kakoshi Kogyo Co., Ltd. (product number: FM-5000, base material: polyolefin resin) (3) DMF masking film manufactured by Daio Kakoshi Kogyo Co., Ltd. (product number: FM-6030, base material: polyolefin resin) (4) Polyester film manufactured by Toray Industries, Inc. (product number: Lumirror S10, base material: PET)

[0080] (3-2. Manufacturing of Laminates) 4 shows a schematic side view of the manufacturing apparatus (400) used to manufacture the laminates of Comparative Examples 3 to 6. The manufacturing apparatus (400) includes a T-die (410) for extruding the fluororesin film (A), a touch roll (420) and a casting roll (430) disposed below the outlet (412) of the T-die (410), a reel (440) for unwinding the protective film (B) onto the touch roll (420), a cooling roll (450) disposed on the side of the casting roll (430), and a reel (490) for winding up the laminate (1). Although not shown, an extruder is disposed above the T-die (410).

[0081] An ECTFE film was extruded from a T-die under the same conditions as in Example 1. The fluororesin film (A) extruded downward from the T-die was sandwiched between a casting roll (430) (cooling water set temperature 40°C) and a protective film (B) on a touch roll (420) (cooling water set temperature 40°C). As a result, the fluororesin film (A) was cooled and solidified, and at the same time, the protective film (B) was peelably laminated to the fluororesin film (A). The laminate (1) thus obtained moved along the rotation direction of the casting roll (430), was then transported onto a cooling roll (450) (cooling water set temperature 30°C) to be cooled, and was finally taken up by a reel (490). The thickness of the fluororesin film (A) shown in Table 1 is the average value measured at any five points with a dial sheet gauge.

[0082] <4. Characterization> (4-1. Peel strength) A sample was taken from the laminate prepared above, and the protective film (B) together with the adhesive layer (C) was peeled off from the fluororesin film (A) at 180° with a gripping speed of 300 mm / min under an environment of 23°C and relative humidity of 50%, and the average peel strength was measured using a tensile compression tester (Strograph VE1D, manufactured by Toyo Seiki Seisakusho Co., Ltd.) according to the measurement procedure described above. The results are shown in Table 1.

[0083] (4-2. Gakushin-type abrasion test) A sample was taken from the laminate prepared above, and a Gakushin-type abrasion test was performed. Specifically, a sample (200 mm x 25 mm) of the laminate was fixed to a test piece stand, and a friction element (steel wool (Bonstar #0000)) was reciprocated from above the protective film (B) under the conditions of a load of 500 gf, 1000 reciprocations, and a reciprocation speed of 30 reciprocations / min. After the test, the protective film (B) was peeled off, and the fluororesin-based film (A) was visually checked for scratches. Other test conditions were in accordance with JIS P8136:1994. Since Comparative Example 1 and Comparative Example 2 did not have a protective film (B), a Gakushin-type abrasion test was performed on the fluororesin-based film (A). The results are shown in Table 1.

[0084] [Table 1]

[0085] <5. Consideration> Comparative Examples 1 and 2, which did not have a protective film (B), were damaged by abrasion. In Comparative Example 5, the degree of damage was reduced because a protective film was provided. However, damage was partially observed due to the abrasion reaching the fluororesin-based film (A). In Comparative Examples 3 to 6, which did not include the adhesive layer (C), the peel strength between the protective film (B) and the fluororesin-based film (A) was too small, and peeling under its own weight was observed. In contrast, in Examples 1 to 10 in which the protective film (B) and the fluororesin film (A) were laminated with an appropriate peel strength via the adhesive layer (C), the fluororesin film (A) was protected by the protective film (B) and was not damaged by abrasion. In Examples 1 to 10, the protective film (B) was peeled off together with the adhesive layer (C), so that the adhesive layer (C) did not substantially remain on the surface of the fluororesin film (A) after peeling. And, the peel strength of 0.06 N / 25 mm to 0.48 N / 25 mm did not show any defects as in Comparative Examples 3 to 6, but was a peel strength that could be easily peeled off by hand, and the workability during peeling was also excellent. [Explanation of symbols]

[0086] 1, 2 Laminate A Fluoropolymer film containing ethylene monomer units B. Protective film C Adhesive layer E Silicone adhesive layer F Separator 400 Laminate manufacturing equipment 410 T-die 412 Exit 420 Touch Roll 430 Casting Roll 440 Reels 450 Cooling Roll 490 reels

Claims

1. A laminate comprising a protective film (B) peelably attached via an adhesive layer (C) to one or both surfaces of a fluororesin film (A) containing an ethylene monomer unit, wherein the average peel strength when the protective film (B) together with the adhesive layer (C) is peeled from the fluororesin film (A) at 180° at a gripping movement speed of 300 mm / min under an environment of 23° C. and a relative humidity of 50%, is 0.05 N / 25 mm or more and 0.50 N / 25 mm or less; The fluororesin film (A) containing an ethylene monomer unit is a single layer, A laminate, wherein the peel strength between the fluororesin film (A) and the adhesive layer (C) is smaller than the peel strength between the protective film (B) and the adhesive layer (C).

2. 2. The laminate according to claim 1, wherein the fluororesin film (A) is a film containing either one or both of an ethylene-chlorotrifluoroethylene copolymer and an ethylene-tetrafluoroethylene copolymer.

3. 3. The laminate according to claim 1, wherein the adhesive layer (C) has a thickness of 1 to 20 μm, and the protective film (B) has a thickness of 20 to 80 μm.

4. The laminate according to any one of claims 1 to 3, wherein the thickness of the fluororesin film (A) is 50 µm or more and 500 µm or less.

5. The laminate according to any one of claims 1 to 4, wherein the protective film (B) contains one or both of a polyethylene-based resin and a polypropylene-based resin, and the adhesive layer (C) contains a (meth)acrylic adhesive.

6. The laminate according to any one of claims 1 to 5, which is wound into a roll.

7. A film for construction obtained by peeling off the protective film (B) from the laminate according to any one of claims 1 to 6.

8. A membrane structure comprising the architectural film according to claim 7.

9. A building comprising the membrane structure according to claim 8.

10. The laminate according to any one of claims 1 to 6, wherein a protective film (B) is bonded to one surface of a fluororesin-based film (A) via an adhesive layer (C), and a silicone-based adhesive layer (E) is provided on the other surface.

11. The laminate according to claim 10, wherein a separator (F) is attached to the surface of the silicone-based adhesive layer (E) that is not in contact with the fluororesin-based film (A).

12. 12. The laminate according to claim 10 or 11, which is in the form of a tape.

13. A step of preparing a plurality of laminates according to any one of claims 1 to 6; a step of partially peeling off the protective film (B) at each end of the plurality of laminates to expose the fluororesin-based film (A); a step of overlapping and heat-sealing the fluororesin-based films (A) exposed at the respective ends of the laminate to each other to form a bonded body in which a plurality of the laminates are bonded together; A step of extending the joint body on a body; peeling the unpeeled protective film (B) from the bonded body; A method for constructing a membrane structure comprising the steps of:

14. Providing a laminate according to claim 10 or 12; a step of attaching the laminate to a membrane portion of a membrane structure to be repaired so that the silicone-based adhesive layer (E) serves as an attachment surface; peeling the protective film (B) from the laminate attached to the membrane portion; A method for repairing a membrane structure comprising the steps of:

15. Providing a laminate according to claim 11; peeling the separator (F) from the laminate; a step of attaching the laminate to a membrane portion of a membrane structure to be repaired so that the silicone-based adhesive layer (E) serves as an attachment surface; peeling the protective film (B) from the laminate attached to the membrane portion; A method for repairing a membrane structure comprising the steps of:

Citation Information

Patent Citations

  • Multi-layer polyester protective film and preparation method thereof

    CN106675426A

  • Surface protecting material for synthetic resin plate

    JP1984093775A

  • Bonded sheet material

    JP1997183159A

  • Fluoroplastic laminated film

    JP1999268204A

  • Photocatalytic hydrophilic film

    JP2001138433A